FRI0495 Magnetic resonance imaging may be helpful in predicting long term efficacy of certolizumab pegol in patients with active rheumatoid arthritis. (23rd January 2014) - Olech, E.; Peterfy, C.; DiCarlo, J.; Sagliani, J.; Genovese, A.; Gaylis, N.
Abstract : Background: Certolizumab pegol (CZP) significantly improved signs and symptoms of RA in a diverse group of patients, including 37.6% who previously used a TNF inhibitor. 1 Objectives: To evaluate short-term non-contrast low-field MRI for predicting long-term efficacy of CZP in patients with moderate to severe active RA who failed at least one non-biologic or biologic DMARD. Methods: In this 2-center open-label study, 20 adult RA pts with DAS > 4.4, on stable dose of MTX, received CZP 400 mg at week (wk) 0, 2 and 4, followed by 200 mg every two wks for 52 wks. All patients had unilateral hand and wrist non-contrast MRI using 0.2 T extremity unit at baseline, 6wk, 16wk and 52wk. The images were scored according to the RAMRIS system and 9-point cartilage loss (CL) scale by a radiologist blinded to visit order. Results: Baseline patients' characteristics were as follows: Mean (SD) age 52.2 (16.9) years old, 70% female, Mean (SD) disease duration 7.3 (5.6) years, 50 % of pts were RF+, 60% anti-CCP+. Mean (SD) MTX dose was 17.25 (3.0) mg/week, Prednisone 2.5 (5.0) mg, 85% of pts were previously on a biologic. Tender/Swollen Joint Count (out of 68/66) was 34/16. Mean (SD) HAQ 4.38 (1.68), DAS28 6.60 (1.06), DAS28CRP 5.74 (0.66). 16/20 pts completed 52 wks. No serious adverse events were reported in this patient population. DAS28 and RAPID scores were significantly reduced at wks: 6, 12, 16, 24, 40, 48 and 52 compared with baseline (Wilcoxon; p<0.001). ACR20/50/70 response rates at 16 & 52 wks (with non-completers considered as non-responders) were 60/30/15 & 45/30/20 %, respectively. At wk 12, 80% and at wk 52, 69% of pts achieved moderate or good EULAR response. Only two pts achieved low disease activity (DAS<3.2) at wk 52. 80% of patients had a DAS28 improvement of ≥ 1.2 by week 12. Of these, 25% did not achieve EULAR response at wk 52. None of the remaining 20% of pts with DAS28 improvement < 1.2 by wk 12, had a EULAR response at wk 52. 52-wk EULAR responders had significantly higher improvement in the OST scores at 16 wks, as compared to non-responders (p= 0.043). Changes in SYN, ERO or CL scores did not differ substantially between the two groups (Figure 1 ). All pts who improved their OST scores by wk 16, were clinical responders at wks 12 and 52. 12-wk clinical responders had 73% probability of EULAR response at wk 52, but if they also had 16-wk OST improvement, the probability was 100% (PPV=1.0). Conversely, if OST worsened, the probability of achieving EULAR response at 52 wks was only 33% (NPV = 0.66). Image/graph: Conclusions: In this preliminary study of an active RA population who failed at least one DMARD and included 85% of pts who previously used a biologic, improvement of osteitis on MRI predicted long-term clinical response to CZP. This finding may be particularly significant in determining therapeutic choices in patients with RA who have previously used a biologic. Our observations were based on a small patient population and suggest a trend without statistical relevance. Larger studies should be done to confirm these findings. References: Weinblatt ME, et al. Rheumatol. 2012; Østergaard M, et al. J Rheumatol. 2003; Peterfy C, et al. Arthritis Res Ther. 2012 Disclosure of Interest: E. Olech Grant/research support from: Abbvie, Genentech, Pfizer, UCB, Vertex, Consultant for: Abbvie, Janssen, Pfizer, UCB, Speakers bureau: Abbvie, UCB, C. Peterfy Shareholder of: Spire Sciences, LLC, Grant/research support from: Amgen, Centocor / Janssen, Pfizer / Wyeth, Abbott, Roche, Genentech, Bayer, Consultant for: Abbott, Articulinx, Merck/ Schering-Plough, Roche, UCB, Pfizer / Wyeth, AstraZeneca, Bristol Myers-Squibb, BioClinica, Celgene, Genentech, Icon Medical Imaging, Lilly, Medimmune, Moximed, Novartis, Perceptive Informatics, VirtualScopics, Jannsen, Genzyme/Sanofi, Biogen-Idec, Employee of: Spire Sciences, LLC, J. DiCarlo Consultant for: Abbott, Amgen, AstraZeneca, BioClinica, Biogen-Idec, Bristol-Myers Squibb, Celgene, Centocor, Core Lab Partners, Crescendo, Eli Lilly, Genentech, Genzyme, Icon Medical Imaging, Johnson & Johnson, Merck, Novartis, Perceptive Informatics, Pfizer, Rigel, Roche, Sanofi, Samsung, UCB, VirtualScopics, Wyeth, Employee of: Spire Sciences, LLC, J. Sagliani: None Declared, A. Genovese: None Declared, N. Gaylis Grant/research support from: Genentech Roche, BMS, UCB, Consultant for: UCB, Speakers bureau: Janssen, UCB